Perioperative and Pathological Outcome of Nerve-Sparing Radical Cystectomy With Ileal Neobladder - Vogt, Katharina; Netsch, Christopher; Becker, Benedikt; Oye, Sebastian; Gross, Andreas J.; Rosenbaum, Clemens M. (Frontiers in Surgery, 2021)
Purpose: So far, it has not been described whether the perioperative course and the pathologic outcome of patients who undergo radical cystectomy (RC) with orthotopic bladder substitution differs if nerve sparing (NS) is performed or not. Material and Methods: In all, there were 472 patients who underwent RC between 2012 and 2019 at our department. We performed a retrospective analysis of 116 patients who underwent RC with ileal neobladder. We analyzed perioperative complications according to the Clavien–Dindo classification system, as well as the pathological outcome. Results: Of 116 patients, 68 (58.6%) underwent RC, and 48 (41.4%) underwent NS RC. Clavien–Dindo complications ≥3b occurred in 15 (12.9%) of all patients. Only infectious complications differed among the groups [NS RC: 25 patients (52.1%) vs. RC: 20 patients (29.4%); p = 0.02]. There was no significant difference concerning tumor stage. Concomitant Cis was present in 24 patients (35.3%) of the RC group and in 27 patients (56.3%) of the NS RC group (p = 0.036). Nodal status and positive surgical margin status of the bladder tumor did not differ among the groups. In all, 42 of all male patients (45.7%) had an incidental prostatic carcinoma. Positive surgical margins concerning the prostate carcinoma occurred in six patients, with all cases in the RC group (p = 0.029). Conclusions: Our data suggest that performing NS during RC in carefully selected patients is a safe procedure and does not impair perioperative outcome. Pathological outcome of NS RC is comparable as well.